2007
DOI: 10.30843/nzpp.2007.60.4675
|View full text |Cite
|
Sign up to set email alerts
|

Natural enemies of Japanese honeysuckle <i>Lonicera japonica</i> in New Zealand

Abstract: Japanese honeysuckle is rapidly increasing as a weed throughout most of the North Island and northern South Island of New Zealand. A classical biological control programme was initiated in 2004-2005 with a survey of the natural invertebrate fauna and pathogens associated with the weed in New Zealand. The honeysuckle was being attacked by a diverse range of native and introduced invertebrates. But overall the damage was minimal and none of the herbivore niches on the weed were well utilised implying that exotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…pisi, Mycosphaerella pinodes, Rhizoctonia solani, and Sclerotinia sclerotiorum pathogens, which cause root rot complex in field peas, and increased both the emergence and yield against these pathogens (Xue, 2003). Since E. purpurea and L. japonica plants are affected by many fungal pathogens (Waipara et al, 2007), we suggest that treatment with LS.B11 and EF.B3 could be used to control these fungal pathogens.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…pisi, Mycosphaerella pinodes, Rhizoctonia solani, and Sclerotinia sclerotiorum pathogens, which cause root rot complex in field peas, and increased both the emergence and yield against these pathogens (Xue, 2003). Since E. purpurea and L. japonica plants are affected by many fungal pathogens (Waipara et al, 2007), we suggest that treatment with LS.B11 and EF.B3 could be used to control these fungal pathogens.…”
Section: Resultsmentioning
confidence: 95%
“…and Pythium sp. (Waipara et al, 2007). Therefore, we tested the biocontrol activities of LS.B11 and EF.B3 against fungal phytopathogens by using in vitro growth inhibition of fungal disc in the presence of endophytes.…”
Section: In Vitro Antifungal Activity Of Lsb11 and Efb3 Against Phymentioning
confidence: 99%
“…In a recent survey of L. maackii shrubs conducted around Cincinnati, OH, USA, 61.8% of L. maackii stems were dead, which was approximately 58% more than found in reports from 1989 (3.2%; Boyce et al 2014). Thus far, there has been no studies, to our knowledge, on biocontrol agents for L. maackii; however, a study by Waipara et al (2007) demonstrated herbivore and pathogen damage was low on Japanese honeysuckle (Lonicera japonica Thunb.) in New Zealand and suggested further research on natural enemies in the native L. japonica range is necessary for the development of biocontrol agents.…”
Section: Lonicera Maackii Effects On Ecosystem Processesmentioning
confidence: 89%
“…A dissecting microscope was used to search necrotic areas for sporulation of P. tuberculatum and other pathogens. Methods outlined previously (Waipara et al 2007) were used to isolate other pathogenic fungi from diseased tissues. Small pieces of tissue were cut from the leading edge of diseased areas, surface sterilised in 2% sodium hypochlorite for 1 min and plated onto potato dextrose agar (Difco Labs, Detroit, MI, USA) amended with 0.02% streptomycin (Sigma, St Louis, MI, USA).…”
Section: Survey Of Foliar Pathogens On Lantana In New Zealandmentioning
confidence: 99%